2018
DOI: 10.3390/polym10101132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Composition Variant and Oxygen Plasma Treatments on the Wettability of PLGA Thin Films, Synthesized by Direct Copolycondensation

Abstract: The synthesis of high molecular weight poly (lactic-co-glycolic) acid (PLGA) copolymers via direct condensation copolymerization is itself a challenging task. Moreover, some of the characteristic properties of polylactide (PLA)-based biomaterials, such as brittleness, hydrophobicity, and longer degradation time, are not suitable for certain biomedical applications. However, such properties can be altered by the copolymerization of PLA with other biodegradable monomers, such as glycolic acid. A series of high m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 55 publications
(72 reference statements)
5
32
0
Order By: Relevance
“…5 (a). Previous studies indicated that PLLA was a relatively hydrophobic material with a very low water uptake [ 42 ], while PGA was relatively hydrophilic material with a very high water uptake [ 43 ]. The water absorption of the PLLA/PGA/HAP scaffolds changed with ratios of PLLA/PGA, and it increased with increasing content of PGA.…”
Section: Resultsmentioning
confidence: 99%
“…5 (a). Previous studies indicated that PLLA was a relatively hydrophobic material with a very low water uptake [ 42 ], while PGA was relatively hydrophilic material with a very high water uptake [ 43 ]. The water absorption of the PLLA/PGA/HAP scaffolds changed with ratios of PLLA/PGA, and it increased with increasing content of PGA.…”
Section: Resultsmentioning
confidence: 99%
“…Even if natural substances such as collagen and fibrin [48] are more biocompatible, many synthetic polymers have been used in tendon tissue engineering such as PCL [14,49], PLLA [47,50], chitosan [51], a mixture of polymer PLLA/PCL [52], PCL/Gel [53,54], and PLGA, which has been widely used in tendon tissue engineering [16,40,[55][56][57]. This material has been chosen to fabricate the fleece used in this work since it is FDA-approved and provides sufficient control of degradation [58,59] combined with a sufficient mechanical strength that fosters its application for tissue remodeling and regeneration [60,61]. Moreover, in a previous study it has been demonstrated that PLGA is highly biocompatible for oAECs, the cells chosen to test the fabricated fleeces, and that the chemistry of the fleece influences their penetration and distribution within the construct, efficiently sustaining and stimulating cell adhesion, viability, and proliferation [62].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of this technique rely on the possibility to control and tune all process parameters avoiding in turn nanofibrous structure damages [29]. Different working gases such as air, oxygen (O 2 ), nitrogen (N 2 ), ammonium (NH 3 ), argon (Ar), or helium (He) have been used for this purpose [29,[43][44][45][46][47][48]. Most of studies concerning plasma activation of electrospun scaffolds have focused on PCL [29,46,47,[49][50][51] and PLLA [52][53][54][55][56][57][58] while those concerning PLGA [48,[59][60][61][62] are few and still neglected in the literature although its wide application range in the field of tissue engineering [63].…”
Section: Introductionmentioning
confidence: 99%